Rastelli operation for double outlet right ventricle, pulmonary atresia with ductal dependent pulmonary flow - Panthee, Nirmal; Pradhan, Sidhartha; Koirala, Raamesh; Pokhrel, Bishow; Thapaliya, Deekshya; Thakur, Apurba; Jha, Ujjwal; Timala, Rabindra (Nepalese Heart Journal, 2021)
Double outlet right ventricle (DORV) with or without pulmonary atresia is a common indication for Rastelli operation. We very infrequently perform this surgery in our center. Here, we report a case of a ten-year-old girl who recently underwent Rastelli operation and patent ductus arteriosus (PDA) ligation for DORV, pulmonary atresia with ductal dependent pulmonary circulation by using custom-made valved conduit